Prospects and Challenges of Bacteriophage Substitution for Antibiotics in Livestock and Poultry Production - Aoyu Jiang; Zixin Liu; Xiaokang Lv; Chuanshe Zhou; Tao Ran; Zhiliang Tan (Biology, 2024)
The overuse and misuse of antibiotics in the livestock and poultry industry has led to the development of multi-drug resistance in animal pathogens, and antibiotic resistance genes (ARGs) in bacteria transfer from animals to humans through the consumption of animal products, posing a serious threat to human health. Therefore, the use of antibiotics in livestock production has been strictly controlled. As a result, bacteriophages have attracted increasing research interest as antibiotic alternatives, since they are natural invaders of bacteria. Numerous studies have shown that dietary bacteriophage supplementation could regulate intestinal microbial composition, enhance mucosal immunity and the physical barrier function of the intestinal tract, and play an important role in maintaining intestinal microecological stability and normal body development of animals. The effect of bacteriophages used in animals is influenced by factors such as species, dose, and duration. However, as a category of mobile genetic elements, the high frequency of gene exchange of bacteriophages also poses risks of transmitting ARGs among bacteria. Hence, we summarized the mechanism and efficacy of bacteriophage therapy, and highlighted the feasibility and challenges of bacteriophage utilization in farm animal production, aiming to provide a reference for the safe and effective application of bacteriophages as an antibiotic alternative in livestock and poultry.